Value Inovasi Pelayanan Dukcapil melalui Aplikasi Slawe - Patrisia, Novliza Eka; Yuliani, Hafri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to describe the public value of the Civil Registration Agency (Dukcapil) innovation through the Slawe application in Bengkulu City. Slawe is an innovation in population services, such as ID cards (KTP), family cards (KK), birth certificates, etc. This innovation represents an effort to improve public services undertaken by the Bengkulu City Government to expedite emergency response in Bengkulu City. This study utilizes Mark Moore's theory of public value. The research method used is descriptive qualitative. Informants were selected through purposive sampling and snowball sampling. The results indicate that the population service, in the form of the Slawe application, aligns with the strategic triangle of public value: legitimacy and support, operational capability, and substantive value. In conclusion, the application's implementation has been supported by strong legitimacy in the form of regulations regarding application use, specifically mayoral rules, and positive public trust. Adequate human resources, technology, and financial resources support operational capability. This service's substantial value is helpful in emergency management and has economic, socio-cultural, political, educational, and ecological value. Keywords: Slawe Application, e-Government, Service Innovation, Public Value, Digital Public.